DECISION MAKING MODELING OF CONCRETE REQUIREMENTS - George Ilinoiu (Civil Engineering Dimension, 2001)
This paper presents the results of an experimental evaluation between predicted and practice concrete strength. The scope of the evaluation is the optimisation of the cement content for different concrete grades as a result of bringing the target mean value of tests cubes closer to the required characteristic strength value by reducing the standard deviation. Abstract in Bahasa Indonesia : concrete+mix+design%2C+acceptance+control%2C+optimisation%2C+cement+content.